(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A species of Megaphragma, new for Italy, has been collected with yellow sticky traps placed in a vineyard in Southern Italy (Basilicata). A preliminary description of this species, which belongs to the group ghesquierei Nowicki and is probably new to science, is given.